2010
DOI: 10.1159/000322535
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Rapidly Attenuates ATP-Evoked Transient Currents in Cultured Rat Dorsal Root Ganglion Neurons

Abstract: Background: Progesterone has been shown to play a role in pain perception. However, the effects of progesterone on P2X3 receptors, the nociception-related receptors in primary sensory neurons, remain unclear. Methods: We investigated the effects of progesterone on P2X3-receptor-mediated responses of rat dorsal root ganglion neurons by using whole-cell patch clamp techniques. Results: Progesterone (10 pmol/l to 1 µmol/l) inhibited ATP (100 µmol/l)-induced transient currents and the transient component of biphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 121 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…While the study of the mechanisms of the antinociceptive effect of progesterone on this model is beyond of the scope of this paper, one could speculate about the involvement of genomic and non-genomic effects. Among the non-genomic mechanisms, it is interesting to note that progesterone directly inhibits ATP-evoked P2X3 receptor-dependent inward currents (Fan et al, 2011), which are well-established players in muscle pain (Shinoda et al, 2008; Dessem et al, 2010). Long-lasting effects of progesterone may be related to additional genomic mechanisms, such as those involved in progesterone-induced inhibition of cytokine-mediated inflammation (Davies et al, 2004), which are known to contribute to endometriosis pain (Giudice, 2010; Umezawa et al, 2008; McKinnon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the study of the mechanisms of the antinociceptive effect of progesterone on this model is beyond of the scope of this paper, one could speculate about the involvement of genomic and non-genomic effects. Among the non-genomic mechanisms, it is interesting to note that progesterone directly inhibits ATP-evoked P2X3 receptor-dependent inward currents (Fan et al, 2011), which are well-established players in muscle pain (Shinoda et al, 2008; Dessem et al, 2010). Long-lasting effects of progesterone may be related to additional genomic mechanisms, such as those involved in progesterone-induced inhibition of cytokine-mediated inflammation (Davies et al, 2004), which are known to contribute to endometriosis pain (Giudice, 2010; Umezawa et al, 2008; McKinnon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ma group reported that 17β‐estradiol and progesterone rapidly attenuate ATP currents in DRG neurons via a cAMP‐PKA signaling pathway. 38 , 39 On contrary, PGE2 enhances P2X3 receptor‐mediated currents in DRG neurons via its EP3 receptor and a cAMP/PKA‐dependent signaling pathway. 40 It has been also reported that PKC and PKA potentiate α,β‐meATP‐induced currents in rat DRG neurons in a synergistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that P2X3 receptor‐mediated ATP currents are regulated by intracellular cAMP/PKA signaling. Ma group reported that 17β‐estradiol and progesterone rapidly attenuate ATP currents in DRG neurons via a cAMP‐PKA signaling pathway 38,39 . On contrary, PGE2 enhances P2X3 receptor‐mediated currents in DRG neurons via its EP3 receptor and a cAMP/PKA‐dependent signaling pathway 40 .…”
Section: Discussionmentioning
confidence: 99%